Prophylactic Antibiotic Use Prior to Port Placement and Its Effect on Insertion-Related Infection Rates: A Five-Year Retrospective Review - Hubert E. Smith; Saher S. Sabri; Neil K. Jain; Zuby J. Syed; Quang H. Nguyen; Donna C. Buckley (The Arab Journal of Interventional Radiology)
Purpose The aim of this study was to compare insertion-related port infection rates between patients who received intraprocedural prophylactic antibiotics versus those who did not.